Analysis and Modelling of Joint ChannelProperties from Multi-site, Multi-Antenna RadioMeasurements - Jalden, Niklas (KTH, Signalbehandling, 2010)
Future wireless communication systems will utilize the spatialproperties of the wireless channel to improve the spectralefficiency and thus increase capacity. This is realized bydeploying multiple antennas at both the transmitter and receiver.Development and analysis of communication systems utilizing thespatial properties of the channel requires channel models thatproperly reflect these characteristics. Due to the unpredictable nature of the wireless channel, a commonapproach is to model its effects statistically. A few largeworld-wide cooperations, like the third generation partnershipproject (3GPP) or wireless world initiative new radio (WINNER)project, have developed channel models intended for reference andstandardization use. These models are partly based on some bulkparameters that describe the characteristics of the channel overlarger areas of several wavelengths. Such parameters includeshadow fading, angle spread, and delay spread, among others, andare within the WINNER project called large-scale (LS) parameters.In the spatial channel model (SCM) and the WINNER model, theselarge-scale parameters are, however, assumed independent betweenseparate links, i.e., between channels modelling the propagationbetween one mobile and several base stations, or between one basestation and several mobiles. Such assumptions may be valid forsingle-link, singe-cell systems, where each communication link issufficiently separated in either time or frequency. In practice,dependencies between parameters describing separate wirelesschannels is expected. Future systems will allow a dense frequencyreuse, and results from system evaluations based on models withindependent links may be inaccurate. Examples of this may be insystems that exploit the spatial nature of the channel, likemulti-user scheduling using a single carrier, or macro-diversitysystems deploying several base stations. Therefore, it isimportant to analyze multi-node measurements in order to extractand characterize this channel dependence. This thesis focuses on representing the wireless channelstatistically. Through unique multi-site channel measurements andanalysis, key parameters describing the channel namely shadowfading, delay spread and angle spread at both the base station andthe mobile station are extracted. For these parameters, the firstand the second order statistics are derived, and plausibledistributions and models are proposed. Further, the spatial andcorrelation properties of these parameters are analyzed. Moreover,a study highlighting the effect of the independent channelassumption is given, showing the importance of modelling thespatial dependence between the LS parameters when analyzingsystems that utilize the channel's spatial properties.Incorporating the models and correlation properties found hereinfor the LS parameters results in channel models appropriate formulti-node communication analysis and evaluation. === QC20100720 === ACCESS